A 6&1-FEH encodes an enzyme for fructan degradation and interact with invertase inhibitor protein in maize (Zea mays L.) - Zhao, Hongbo; Greiner, Steffen; Rausch, Thomas (International journal of molecular sciences, 2019)
About 15% of higher plants have acquired the ability to convert sucrose into fructans. Fructan degradation is catalyzed by fructan exohydrolases (FEHs), which are structurally related to cell wall invertases (CWI). However, the biological function(s) of FEH enzymes in non-fructan species have remained largely enigmatic. In the present study, one maize CWI-related enzyme named Zm-6&1-FEH1, displaying FEH activity, was explored with respect to its substrate specificities, its expression during plant development, and its possible interaction with CWI inhibitor protein. Following heterologous expression in Pichia pastoris and in N. benthamiana leaves, recombinant Zm-6&1-FEH1 revealed substrate specificities of levan and inulin, and also displayed partially invertase activity. Expression of Zm-6&1-FEH1 as monitored by qPCR was strongly dependent on plant development and was further modulated by abiotic stress. To explore whether maize FEH can interact with invertase inhibitor protein, Zm-6&1-FEH1 and maize invertase inhibitor Zm-INVINH1 were co-expressed in N. benthamiana leaves. Bimolecular fluorescence complementation (BiFC) analysis and in vitro enzyme inhibition assays indicated productive complex formation. In summary, the results provide support to the hypothesis that in non-fructan species FEH enzymes may modulate the regulation of CWIs.